2022 IEEE International Conference on Image Processing (ICIP) 2022
DOI: 10.1109/icip46576.2022.9897356
|View full text |Cite
|
Sign up to set email alerts
|

On Adversarial Robustness of Deep Image Deblurring

Abstract: Recent approaches employ deep learning-based solutions for the recovery of a sharp image from its blurry observation. This paper introduces adversarial attacks against deep learningbased image deblurring methods and evaluates the robustness of these neural networks to untargeted and targeted attacks. We demonstrate that imperceptible distortion can significantly degrade the performance of state-of-the-art deblurring networks, even producing drastically different content in the output, indicating the strong nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The latter mainly uses input-output model queries to generate adversarial samples, e.g., ZOO [36], SimBA [22], GeoDA [37], and Square Attack [23]. Attackers are not only targeting computer vision tasks [38]- [40], but are also trying to harm other DNN-based tasks, such as natural language processing [41] and image generation [42].…”
Section: B General Adversarial Attacks and Defensesmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter mainly uses input-output model queries to generate adversarial samples, e.g., ZOO [36], SimBA [22], GeoDA [37], and Square Attack [23]. Attackers are not only targeting computer vision tasks [38]- [40], but are also trying to harm other DNN-based tasks, such as natural language processing [41] and image generation [42].…”
Section: B General Adversarial Attacks and Defensesmentioning
confidence: 99%
“…Recent research has explored the topic of adversarial attacks in low-level image restoration tasks, such as derain [52], superresolution [53]- [55], dehaze [40], deblur [38], and reflection removal [56]. Yu et-al.…”
Section: Adversarially Robust Image Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Antun et al [6] observed that deep learning for inverse problems comes with instabilities in the sense that ,,tiny, almost undetectable perturbations, both in the image and sampling domain, may result in severe artifacts in the reconstruction", while Genzel et al [16] attested in their comprehensive tests that ,, deep-learning-based methods are at least as robust as TV minimization with respect to adversarial noise". The authors of [15] showed experimentally the sensitivity of NN to perturbations for the inverse problem of image deblurring.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 settings. Recently, adversarial attacks have also been investigated for CT imaging 19,20. While our work is not concerned with fooling DNNs via adversarial examples, we will see in Sec.…”
mentioning
confidence: 99%